THE LACK OF THE THEORY OF TEACHING METHODS OF THE INTERPRETATION OF THE NOVEL (Heritage, 2023)
This paper deals with the research of a complete teaching question of reading literary text. Reading literary works is a way of introducing into the art of words and a renewal for knowing science about it. The school reads and processes, the literary texts of all genres. Since the novel is a great prose text, the text of Northern hundred pages - its reading and schoolwork/study involve the most hours, work at home and in the school, not only by volume, but by generalization of numerical esthetic, philosophical, psychological and sociological and linguistic potentials and ideas - the novel is motivated by self-reading and thinking, encourages, more than other genres, to actively participate in processing and analysis in basic and interpretation and study in high school. The methodical theory of the interpretation of novels in the school was created with the growing needs of teaching practice, and the school interpretation of the novel was shaped and harmonized with the flows of the methodical theory of teaching the novels. The paper presents our research of Serbian language and literature, curriculum, textbook history, tekstbook theory and literature teaching methodology, and based on the obtained data points to shortcomings in teaching practice, offering solutions for better teaching practice.
Keywords: territory, methodology, teaching, novel, school